Macroeconomic Stabilization Policies from the Lessons of the Covid-19 Pandemic: Evidence from A Survey in Vietnam - Vu Thi Anh Huyen (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2026)
Backgrounds: The pandemic is not only a health shock but also a systemic macroeconomic shock, transmitting simultaneously through the real sector, fiscal policy, the financial-credit system, and the external sector. Objectives: This paper aims to examine policy priorities for stabilizing the macroeconomy in the context of a pandemic. Methodology: The study utilizes survey data collected from 569 respondents in Vietnam to identify perceived transmission channels and policy priorities in both prevention and response phases. Findings: The results show that disruption in the real sector is perceived as the most significant source of macroeconomic instability (40.6%), followed by external shocks (23.4%) and fiscal pressures (21.3%), while financial-credit stress ranks lowest (14.8%). For pandemic prevention, the most widely selected measures include ensuring supply chain and logistics continuity (77.9%), accelerating digital transformation (71.0%), and building fiscal reserves with rapid support mechanisms (68.0%). However, when considering the top priority, strengthening preventive healthcare capacity and epidemiological surveillance ranks first (31.8%). In the response phase, supporting businesses to maintain employment and cash flow (80.7%) and ensuring uninterrupted logistics (67.0%) are the most widely chosen. Yet, evidence-based pandemic control and reducing healthcare system overload are identified as the highest priority (27.8%). Conclusions: The findings suggest that macroeconomic stabilization during a pandemic requires an integrated approach, combining effective health shock control, real-sector resilience, social protection, and coordinated fiscal, monetary, credit, and external policies.